2008
DOI: 10.3748/wjg.14.4684
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis B virus gene expression and replication by artificial microRNA

Abstract: 0.01 for all). In the cells with stable transfection, the secretion of HBsAg and HBeAg into the supernatant was significantly inhibited in all three transfection groups (P < 0.01 for all, vs negative control). The copies of HBV DNA were inhibited by 33.4% ± 3.0%, 60.8% ± 2.3% and 70.1% ± 3.3%, respectively. CONCLUSION: In HepG2.2.15 cells, HBV replication and expression could be inhibited by artificial microRNA targeting the HBV S coding region. Vector-based artificial microRNA could be a promising therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In 2009, it was also found that miRNA-199a played an important role in inhibiting HCV genome replication and may also serve as a novel antiviral therapy [39]. In the same way, vectorbased artificial miRNA that was transfected into HeG2.2.15 cells could inhibit HBV replication, and could be a promising therapeutic approach for HBV infection [40]. Not just the mature miRNA, but pol IIexpressed pri-miR mimics may be useful in the treatment of HBV infection [41].…”
Section: A Novel Therapeutic Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…In 2009, it was also found that miRNA-199a played an important role in inhibiting HCV genome replication and may also serve as a novel antiviral therapy [39]. In the same way, vectorbased artificial miRNA that was transfected into HeG2.2.15 cells could inhibit HBV replication, and could be a promising therapeutic approach for HBV infection [40]. Not just the mature miRNA, but pol IIexpressed pri-miR mimics may be useful in the treatment of HBV infection [41].…”
Section: A Novel Therapeutic Methodsmentioning
confidence: 96%
“…Artificial miRNA-mediated RNA interference (RNAi), based on the murine miR-155, could inhibit HBV protein expression and HBV DNA replication in HepG2.2.15 cells in vitro [15]. In mammals, miR-122 is abundant in liver to help maintain liver tissue identity [16].…”
Section: Cellular Mirnamentioning
confidence: 99%
“…Immunohistochemical detection of HBV core antigen revealed 99% reduction in stained hepatocyres upon RNAi treatment [50]. It was also noticed that HVB replication and expression has been inhibited by artificial microRNA targeting the HBV S coding region in HepG2.2.15 cells [27]. This vector-based artificial microRNA could be a promising therapeutic approach for curing chronic HBV infection.…”
Section: Hepatitismentioning
confidence: 95%
“…The authors proposed that HBV had evolved to use viral miRNAs as a means to regulate its own gene expression to its benefit (40). This hypothesis was confirmed in vitro when vector-based artificial miRNA (amiRNA) successfully inhibited HBV replication and expression (41). Ely et al confirmed the in vivo viability of this potential therapeutic approach to HBV by employing RNA polymerase II promoter cassettes that transcribes anti-HBV primary miRNA shuttles, specifically pri-mi-122 and pri-mi-31, with a resulting decreases in HBV expression (42).…”
Section: Viral Hepatitis Bmentioning
confidence: 95%